2019
DOI: 10.1111/jerd.12495
|View full text |Cite
|
Sign up to set email alerts
|

Color stability and surface roughness of composite resins submitted to brushing with bleaching toothpastes: An in situ study

Abstract: Objective To evaluate, in situ, the color stability (CS) and surface roughness (SR) of composite resins after toothbrushing with whitening toothpaste. Materials and Methods Specimens (6 × 2 mm/) of composite resin (Tetric N‐Ceram, Z250 and Z350) were randomly fixed on thirty participants' upper molars (buccal surface). For an initial standardization (7 days), participants used a soft toothbrush and nonwhitening toothpaste (SDB ‐ Sorrisos Dentes Brancos). Initial CS (Easyshade) and SR (Surfcorder RS) measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 21 publications
6
48
0
1
Order By: Relevance
“…The results showed that, the surface roughness was significantly affected by the dentifrice factor, so rejecting the null hypothesis. This finding agrees with other studies that showed a correlation between tooth brushing with the use of abrasive dentifrice and the increase in the surface roughness of composite (11,12,21) .…”
Section: Effect Of the Dentifricesupporting
confidence: 93%
See 2 more Smart Citations
“…The results showed that, the surface roughness was significantly affected by the dentifrice factor, so rejecting the null hypothesis. This finding agrees with other studies that showed a correlation between tooth brushing with the use of abrasive dentifrice and the increase in the surface roughness of composite (11,12,21) .…”
Section: Effect Of the Dentifricesupporting
confidence: 93%
“…Direct composite resins are always exposed to chemical and mechanical challenges that can alter the material properties such as when associated with long term brushing , specially when the toothpaste contain hard abrasive particles, so the composite resin will degrade and compromise giving opposite results from what was expected from the whiting dentifrices (11,12) . Different dentifrices with different compositions have been developed to improve the affectivity of cleaning and whitening of teeth, Few of them have hydrogen peroxide (1%) in its formulation which is the active principle of bleaching products used in the dental office because it can cause irritation of the gingival tissues and lead to dentin hypersensitivity (18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with previous in situ and in vitro studies, which stated that although there is a luminosity reduction of the composites after brushing with abrasive dentifrices, that alteration is not high enough to change the resin color at all. 19,20 The chemical composition and structure of the base monomer influences the degree of conversion, water sorption, water solubility, and color stability of the restorative material. Past studies have shown that UDMA-based materials exhibit higher color stability than Bis-GMA-based composites.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen peroxide (30-35%) was associated with changes in surface reflectance 13) . Increased surface roughness of hybrid and nanocomposites was found after treatment with whitening toothpastes, likely due to the abrasive effect of toothpastes and not whitening agents 17) .…”
Section: Introductionmentioning
confidence: 96%